2019
DOI: 10.4081/hr.2019.7732
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Mean Platelet Volume for Distinguishing the Causes of Thrombocytopenia in Adult Patients

Abstract: Establishment and analysis of mean platelet volume (MPV) may be helpful in the discrimination between underproduction or over-destruction of platelets as the causes of thrombocytopenia. The primary objective is to find the cut-off point of MPV for distinguishing causes of thrombocytopenia. The secondary objective is to validate the cut-off value of the MPV by using bone marrow examination. Thrombocytopenic patients were enrolled in a training set and a receiving operating characteristics (ROC) curve was plotte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…As these mice also have low platelet counts, their bone marrow is likely compensating for platelet loss on the periphery (Stasi, 2012). This state can be a result of immune‐mediated processes such as immune thrombocytopenia (Schmoeller et al , 2017; Norrasethada et al , 2019). Unfortunately, data concerning mean platelet volume are not available for BBS patients, but we can presume that the peripheral destruction of platelets is a cause of thrombocytopenia in BBS patients as well as in mice.…”
Section: Discussionmentioning
confidence: 99%
“…As these mice also have low platelet counts, their bone marrow is likely compensating for platelet loss on the periphery (Stasi, 2012). This state can be a result of immune‐mediated processes such as immune thrombocytopenia (Schmoeller et al , 2017; Norrasethada et al , 2019). Unfortunately, data concerning mean platelet volume are not available for BBS patients, but we can presume that the peripheral destruction of platelets is a cause of thrombocytopenia in BBS patients as well as in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Since the size of the immature platelets is larger than that of the mature ones, large platelet volume combined with thrombocytopenia indicates active platelet production in the bone marrow compensating for their loss in the periphery [98]. This state can be a result of immune-mediated processes such as immune thrombocytopenia; it is also seen in disseminated intravascular coagulopathy, thrombotic thrombocytopenic purpura, and sepsis [99,100]. Unfortunately, we do not have results of mean platelet volume from BBS patients, but we can presume that the reasons of thrombocytopenia in BBS patients and mice are similar, suggesting a role of the peripheral destruction of platelets.…”
Section: Discussionmentioning
confidence: 99%
“…They established MPV cutoff values to be ranging from ≥ 9 fl to ≥ 11 fl in hyperdestructive group. Study done by Norrasethada et al [1] and Numbenjapon et al [18] suggested a MPV cutoff of ≥8.8 fL and ≥ 7.9fl, respectively, for differentiating hyperdestructive and hypoproductive groups. However, Borkataky et al [19] found no significant difference in MPV values between the hyperdestructive thrombocytopenia group and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets were first discovered by Giulio Bizzozero way back in 1882. [1] A platelet count <1.5 lakhs/cumm is defined as thrombocytopenia which is the most common cause of abnormal bleeding. Clinical symptoms vary ranging from easy bruising to life-threatening, based on the severity of thrombocytopenia.…”
Section: Introductionmentioning
confidence: 99%